Pengaruh Kualitas Layanan Terhadap Kepuasan, Kepercayaan dan Loyalitas Pelanggan pada E-Commerce (Studi Kasus : Shopee) - Yusrini Meidita; Suprapto Suprapto; Retno Indah Rokhmawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Shopee is one of the youngest e-commerce that is growing rapidly in the online buying and selling market. This mobile apps marketplace officially operating in Indonesia on 2015 and on 2018 Shopee has been achieved 1.5 million transactions within 24 hours on June which is a new record for the e-commerce marketplace in Indonesia. However by having the marketing strategy are Warranty strategy, Free Shipping and Cheapest Price Guarantee, there are still many reviews from users taht this application is still less satisfactory such as application error complaints, inaccurate order tracking, payment features, Shopeepay wallets and product images that often do not appear. This study aims to determine the quality of service in affecting customer satisfaction, trust and loyalty to Shopee. Respondents in this study are consumers who have made purchases of products at Shopee. The model used in this study adapted the model of Kasim Abdullah who has five dimensions on Service Quality namely Ease of Use, Web Design and Layout, Responsiveness, Perrsonalization, Assurance that affect the Trust, Word of Mouth and Intention. This study used a sample of 100 respondents with quota sampling technique. This study was tested using PLS-SEM and evaluated the model by using Measurement Model and Structural Model to know the quality and significant influence to the constituents that have been hypothesized. From the results of the study showed that from the five dimensions of Service Quality there are two dimensions of Ease of Use and Layout that does not significantly affect Satisfaction. Satisfaction positively affects Trust and Intention but does not affect word-of mouth.Trust affects Word-of-mouth but does not positively affect Intention, and last word-of mouth positively affects Intention.